Automated Life cycle inventories for existing buildings – a parametric reference model approach. Issue 1 (1st September 2022) - Kanafani, K; Garnow, A; Zimmermann, R; Sørensen, C; Stapel, E; Birgisdottir, H
Abstract: Buildings account for 40% of global Greenhouse gas (GHG) emissions. In heating-dominated climates, most building-related emissions originate from building stock operational energy, especially from buildings constructed before energy requirements were introduced. Renovation can mitigate operational emissions, however, materials should be included to increase the mitigation potential. Life-cycle assessment (LCA) includes emissions from materials and energy but are time-consuming in renovations because BIM-aided approaches for automating inventories are inaccessible for existing building fabric. This paper proposes a parametric inventory-generator for existing buildings, which defines material quantities through few key variables, which are accessible in early design stages, and which relate to a reference model for a specific building type. The generated model includes LCA inventory data such as service life, replacements, and End of Life from a generic impacts database. The model is adjustable and can be supplied with predefined renovation interventions and new components. The proposed simplification has potential to facilitate modelling of LCA inventories for every existing building, and makes LCA feasible for more than deep renovations, offering a base for the proposed renovation pass by the EU commission. Future research will add building types and explore implementing default inventories based on cadastre data as public resource.